Oral Administration of Cogongrass (Imperata cylindrica L) Root Ethanol- Extract causes Mouse Epididymal Sperm Abnormality (PEMBERIAN EKSTRAK ETANOL AKAR ALANG-ALANG (IMPERATA CYLINDRICA L) SECARA ORAL MENYEBABKAN ABNORMALITAS SPERMA EPIDIDYMIS MENCIT) - Widyastuti, Rini; Sudiman, Jaqueline; Tyagita, Tyagita; Syamsunarno, Mas Rizky Adipurna Anggun; Sumarsono, Sony Heru (Jurnal Veteriner; Vol 19 No 3 (2018), 2018)
Sperm morphology is an important parameter to be observed in the male fertility. Some of the bioactive compounds of cogongrass root such as alkaloid and terpenoid, affect male fertility by interference the spermatogenesis. The objective of the study was to observe the effect of cogongrass root ethanol extract on mouse sperm morphology. This study was carried out by oral administration of two different doses i.e 90 and 115 mg/kg body weight of cogongrass root ethanol extract into 8-10 weeks old DDY strain mice for 14 days to evaluated the acute effect due to the administration of cogongrass root ethanol extract on mouse sperm morphology. The results showed that treatment with cogongrass root ethanol extract significantly increased sperm abnormalities followed a dose depending pattern (p<0.05). Interestingly, the administration of cogongrass root extract did not affect sperm head morphology but tailless, folded and bent sperm increased linearly with the administration dose of cogongrass root ethanol extract. In conclusion, cogongrass root ethanol extract causes  secondary sperm abnormalitties on mouse sperm.